Predictors of Quality of Life in Acromegaly: No Consensus on Biochemical Parameters - Geraedts, Victor J.; Andela, Cornelie D.; Stalla, Günter K.; Pereira, Alberto M.; van Furth, Wouter R.; Sievers, Caroline; Biermasz, Nienke R. (Frontiers in Endocrinology, 2017)
BACKGROUND Quality of life (QoL) in patients with acromegaly is reduced irrespective of disease-state. The contributions of multifactorial determinants of QoL in several disease stages are presently not well known. OBJECTIVE To systematically review predictors of QoL in acromegalic patients. METHODS Main databases were systematically searched using predefined search terms for potentially relevant articles up to January 2017. Inclusion criteria included: separate acromegaly cohort, non-hereditary acromegaly, QoL as study parameter with clearly described method of measurement and quantitative results, N≥10 patients, article in English and adult patients only. Studies were included using the PRISMA flow diagram. RESULTS We identified 1162 studies; 51 studies met the inclusion criteria: 31 cross-sectional observational studies (mean AcroQoL score 62.7 (range 46.6 – 87.0, n=1597)), 9 had a longitudinal component (mean baseline AcroQoL score 61.4 (range 54.3 – 69.0, n=386)) and 15 were intervention-studies (mean baseline AcroQoL score 58.6 (range 52.2 – 75.3, n=521)). Disease-activity reflected by biochemical control measures yielded mixed, and therefore inconclusive results with respect to their effect on QoL. Addition of pegvisomant to somatostatin analogs and start of lanreotide autogel resulted in improvement in QoL. Data from intervention-studies on other treatment modalities were too limited to draw conclusions on the effects of these modalities on QoL. Interestingly, higher BMI and greater degree of depression showed consistently negative associations with QoL. Hypopituitarism was not significantly correlated with QoL in acromegaly. CONCLUSION At present, there is insufficient published data to support that biochemical control, or treatment of acromegaly in general, is associated with improved QoL. Studies with somatostatin receptor ligand treatment, i.e. particularly lanreotide autogel and pegvisomant have shown improved QoL, but consensus on the correlation with biochemical control is missing. Longitudinal studies investigating predictors in treatment-naive patients and their follow-up after therapeutic interventions are lacking, but are urgently needed. Other factors, i.e. depression and obesity were identified from cross-sectional cohort studies as consistent factors associated with poor QoL. Perhaps treatment strategies of acromegaly patients should not only focus on normalizing biochemical markers, but emphasize improvement of QoL by alternative interventions such as psychosocial or weight lowering interventions.